Communication Patterns in Remote, Interactive Surgical Training. (November 2019) - Shah, Claire S.; Shalin, Valerie L.; Pugh, Kristy; Agandi, Lorreen; Puche, Adam; Tisherman, Sam
The present study examines process and outcome measures associated with three forms of support for conducting an unfamiliar surgical task: an unaided control condition, a video resource condition and a remotely-located mentor. Twenty-eight surgeons performed four different uncommon trauma procedures while thinking aloud in either the control or video condition or exchanging dialogue with an available mentor. Focusing on the upper and lower fasciotomies here, we analyzed verbal content using LIWC metrics and specially composed dictionaries based on Speech Act Theory. Both procedure-specific and subjective performance measures distinguish between experimental conditions, favoring the mentoring condition. Mentor presence also changes the surgeons' verbal data. Verbal data are correlated with the procedure specific performance measures across all conditions but have no relationship to the subjective measure. Focus on the status of the procedure is reinforced by the mentor's presence and indicates potential opportunities for augmenting the video intervention.